Urgensi Peraturan Mengenai Rangkap Jabatan DPR dan Beneficial Owner dalam Perseroan Terbatas - Fadilatin Choirotunnisah; Sumriyah Sumriyah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
In a Limited Liability Company, share ownership can be owned by shareholders whose names are registered in the shareholder register. Over time, shares can also be owned by people specifically appointed to act on behalf of the person who appointed them or the Beneficial Owner. According to Presidential Decree Number 13 of 2018, beneficial owners can participate in the management or not participate in the management, so this position is often used as the right position to gain profits from the Company without participating in the management of the Company, so many people use this position to hold multiple positions. One of them is Setya Novanto, who also serves as Chairman of the DPR, who committed e-KTP corruption, in which case there are no regulations regarding holding the DPR's dual position as a Beneficial Owner. The research method used is a normative research method. The approach method used in this research is the statutory approach and the case approach. The absence of these regulations could worsen the possibility of the Company becoming a money laundering medium.